The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2139/ssrn.1494308
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Wage Mobility in Germany

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
5
8
0
Order By: Relevance
“…The mobility measures discussed in the previous section do not give information about We observe that the probability of remaining in the same quintile increases over time in both two and four-year transitions indicating a decline in mobility over time. Similar observations are found by Dickens (2000) in the UK, Hofer and Weber (2002) in Austria, Cardoso (2006) in Portugal and the UK, Gernandt (2009), Riphahn and Schnitzlein (2011) and Aretz (2013) in East and West Germany. On the other hand, a comparison of Tables 12 and 13 shows that the probability of remaining in the same quintile has decreased.…”
Section: Transitions Between Wage Quintilessupporting
confidence: 75%
“…The mobility measures discussed in the previous section do not give information about We observe that the probability of remaining in the same quintile increases over time in both two and four-year transitions indicating a decline in mobility over time. Similar observations are found by Dickens (2000) in the UK, Hofer and Weber (2002) in Austria, Cardoso (2006) in Portugal and the UK, Gernandt (2009), Riphahn and Schnitzlein (2011) and Aretz (2013) in East and West Germany. On the other hand, a comparison of Tables 12 and 13 shows that the probability of remaining in the same quintile has decreased.…”
Section: Transitions Between Wage Quintilessupporting
confidence: 75%
“…This was likely due to labor market institutions, such as unions, and was consistent with the hypothesis of skill-biased technological change especially in the upper part of the wage distribution (Fitzenberger, 1999). Since the mid 1990s, the lower-tail wage inequality has distinctly risen (Dustmann et Second, Gernandt (2009) shows in one of the very few studies on wage mobility in Germany that earnings mobility declined over the last decades using household panel data from the German Socio-Economic Panel (GSOEP). This finding is confirmed by Riphahn and Schnitzlein (2011), which is to the best of my knowledge the only study that analyzes both the evolution of wage inequality and wage mobility using German administrative data.…”
supporting
confidence: 69%
“…Moreover, more explanatory variables than those covered by this study may influence the development of wage inequality and mobility, as is suggested by, e.g., Gernandt (2009) Nevertheless, the simultaneous observation of increasing wage inequality and decreasing wage mobility clearly calls for a closer consideration of workers earning a low wage as this development gives rise to a larger persistence of low-wage employment. However, the determinants underlying the evolution of low-wage mobility are hardly documented in the literature so far.…”
Section: Long-term Mobility Patternsmentioning
confidence: 64%
“…In their comparison of East and West German income mobility early after unification Hauser and Fabig (1999) find that mobility was initially much higher in East Germany but declined already by 1995. Gernandt (2009) and Bayaz-Ozturk et al (2011) apply SOEP data (1984-2007 for West Germany and find declining mobility, while Bartels and Bönke (2010) find rising earnings volatility among West German males.…”
Section: Introductionmentioning
confidence: 98%